Teaching a language through role-play - Bahriyeva, Nargiza (Linguistics and Culture Review, 2021)
This research examines the importance of role-playing in teaching a language. The technique of role-playing if used right could promote a positive atmosphere among the students in the classroom. After all, the goal of teaching any language is to get the students’ attention by engaging their learning abilities successfully. Therefore, all aspects of teaching through role-playing are explored and guidance is provided on how to use them in the classroom.